Development of SSCS-Based Teaching Materials Integrated with TPACK in Cultivating Students' Scientific Attitudes - Lissa Zikriana; Fatimah; Bulan Nuri (Postgraduate, University of Mataram, 2023)
This study aims to produce teaching materials based on SSCS integrated TPACK and determine the effectiveness of teaching materials based on SSCS integrated TPACK developed in fostering students' scientific attitudes. This type of research is Research and Development (R&D) developed by Borg and Gall. The research location used is SMP Negeri 3 Peusangan. The research subjects amounted to 30 people who were selected using purposive sampling technique. The data collection technique used an expert validation test sheet to measure the validity of SSCS-based teaching materials integrated with TPACK and a questionnaire sheet (questionnaire) to collect feasibility data and students' scientific attitudes. Data analysis was carried out by processing validator response data and Likert scale then converted into qualitative data. Scientific attitude data were analyzed using the N-gain formula. The results showed that the teaching materials based on SSCS integrated TPACK developed were declared valid and feasible for use in learning. Teaching materials based on SSCS integrated TPACK can also foster the scientific attitude of students during learning activities, especially on Newton's Law material.